Symptoms of Dry Eye Disease and Personality Traits - Ichinohe, Sho (PLoS One, 2016)
The essential targets of dry eye disease (DED) treatments include both objective signs and subjective symptoms. However, due to the numerous subjective symptoms, it is understandable why little association has been found between the signs and symptoms. Although psychological influences on the subjective symptoms have been reported, little is known about the influence of personality traits. The present study analyzed the relationship between the signs/symptoms of DED and the personality traits of patients using a cross-sectional design. We examined 56 DED patients (mean age; 62.4 ± 12.9, range 34–85 years) visiting the outpatient clinic of the Department of Ophthalmology at the Nippon Medical School Hospital in Tokyo, Japan. Objective signs evaluated included the Schirmer I test, tear breakup time (BUT), fluorescein and lissamine green staining, and tear osmolality. Subjective symptoms were assessed by the Ocular Surface Disease Index (OSDI) and Dry Eye-Related Quality-of-Life Score (DEQS) questionnaires. For personality traits, the Big Five personality traits model analysis was used. Correlations between the objective signs, subjective symptoms, and personality traits were analyzed. A significant correlation was found between the neuroticism in the Big Five Personality Inventory and the symptoms assessed by the DEQS (r = -0.35, p < 0.01), and the OSDI (r = -0.28, p < 0.05). There was no significant correlation observed between the signs and the symptoms, or between the signs and any personality traits. The results of our current study suggest that the personality of the patient, which appears to be the basis of various psychological factors, can have some impact on the subjective symptoms. This may be one of the reasons why there has been little association noted between the signs and symptoms of DED.